2021
DOI: 10.1177/02654075211059193
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of loneliness across the life span

Abstract: Although loneliness is typically associated with adolescence and old age, research has revealed that it is prevalent across the life span. The present study contributes to the loneliness literature by investigating a broad range of risk factors in a Dutch sample ( N = 52,341) ranging from late adolescence to old age using a cross-sectional survey administered by the regional public health services in the province of Limburg in the Netherlands. Risk factors associated with higher levels of self-reported lonelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 57 publications
0
29
0
8
Order By: Relevance
“…Loneliness refers to not only the state of being lonely but also the feeling of deprivation of social connectedness, which the changing socioeconomic scenarios during the pandemic are likely to affect. Loneliness has long been a public health concern [ 2 , 3 ] with several known risk factors, such as age, gender, lower education levels, inadequate financial resources, and limited social contact or network type [ 4 , 5 , 6 ]. The implementation of health safety measures at varying magnitudes during different phases of the pandemic, along with changes in living conditions, earning capacity, employment status, anxiety, depression, and other factors, have affected people’s psychological conditions, making them more prone to loneliness [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness refers to not only the state of being lonely but also the feeling of deprivation of social connectedness, which the changing socioeconomic scenarios during the pandemic are likely to affect. Loneliness has long been a public health concern [ 2 , 3 ] with several known risk factors, such as age, gender, lower education levels, inadequate financial resources, and limited social contact or network type [ 4 , 5 , 6 ]. The implementation of health safety measures at varying magnitudes during different phases of the pandemic, along with changes in living conditions, earning capacity, employment status, anxiety, depression, and other factors, have affected people’s psychological conditions, making them more prone to loneliness [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another thing to consider is that the findings only focus on one country. This could be problematic because loneliness levels can vary considerably between different regions 20 , 21 , 32 . For example, previous research has demonstrated that Eastern European countries are characterised by a gradual increase of both loneliness and age, whereas Western European countries are associated with a rapid increase in loneliness only after ~ 70 years of age 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although many factors could have contributed to these mixed findings (e.g., sociodemographic and health characteristics of the samples 20 ), in this study we consider two factors that have not received sufficient attention in the research literature. First, the majority of studies have treated loneliness as a unidimensional concept, which could have masked relationships between age and different dimensions of loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations